Johnny Marshall interviewed by Chris Woodland for the Chris Woodland folklore collection - Marshall, Johnny, 1897-1979.; Woodland, Chris, 1938- (1977)
Marshall,of Deep Creek, Araluen reminisces about the Araluen goldfields at the beginning of the 20th century and mentions Alby Matthews, Martin Sullivan and Johnny (Alf?) Greenwood and dances and musical instruments. He then recites, or recites in part, the following poems, "A legend of the Dargo", "Father Riley's horse", "Skeeta", "Wing Fat" and "O'Toole and McSharry".
Background information on interviewee available (1 p.).
Recorded June 1977 at Braidwood, N.S.W.
Digital master available
Corrected transcript available (typescript, 4 leaves)
Keywords: Marshall, Johnny, -- 1897-1979 -- Interviews; Araluen (N.S.W.) -- History